Vitreous hemorrhage in diabetes patients with proliferative diabetic retinopathy undergoing hemodialysis. Issue 3 (9th November 2019) - Kameda, Yusuke; Hanai, Ko; Uchigata, Yasuko; Babazono, Tetsuya; Kitano, Shigehiko
Abstract: Aims/Introduction: For diabetes patients undergoing hemodialysis, vitreous hemorrhage seems to be a hemodialysis‐induced hemorrhagic complication because of the effect of systemic anticoagulation. However, it is unclear whether hemodialysis is associated with vitreous hemorrhage in diabetes patients. We therefore carried out this cohort study to clarify the relationship between hemodialysis and vitreous hemorrhage in diabetes patients with proliferative diabetic retinopathy. Materials and Methods: This was a single‐center, retrospective, cohort study. We compared the incidence of vitreous hemorrhage in non‐vitrectomized proliferative diabetic retinopathy eyes between the hemodialysis group (145 eyes) and peritoneal dialysis group (36 eyes), which does not require the use of systemic anticoagulation (parallel‐group study), and in hemodialysis patients in the 12‐month period before and after the start of hemodialysis (before–after study). We also determined the risk factors for vitreous hemorrhage after the start of hemodialysis based on the patients' systemic and ophthalmic characteristics. Results: There was no significant difference in the first‐year incidence of vitreous hemorrhage between the hemodialysis (23.4%) and peritoneal dialysis groups (22.2%, P  = 1.000). The incidence of vitreous hemorrhage in the dialysis period (23.4%) was significantly lower than that in the predialysis period (35.2%, P  = 0.008). Only application of panretinal photocoagulation within the 6 months immediately before hemodialysis was significantly associated with the incidence of vitreous hemorrhage after the start of hemodialysis ( P  < 0.001). Conclusions: Hemodialysis therapy does not seem to be associated with a higher risk of vitreous hemorrhage in diabetes patients with proliferative diabetic retinopathy. Abstract : This study aimed to determine whether hemodialysis is associated with vitreous haemorrhage in patients with proliferative diabetic retinopathy. These results suggest that hemodialysis therapy does not seem to be a significant risk for vitreous haemorrhage in proliferative diabetic retinopathy patients.